2022
DOI: 10.21203/rs.3.rs-1435729/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detecting SARS-CoV-2 Variants in Wastewater and Their Correlation With Circulating Variants in the Communities

Abstract: Detection of SARS-CoV-2 viral load in wastewater has been highly informative in estimating the approximate number of infected individuals in the surrounding communities. Recent developments in wastewater monitoring to determine community prevalence of COVID-19 further extends into identifying SARS-CoV-2 variants, including those being monitored for having enhanced transmissibility. We sequenced genomic RNA derived from wastewater to determine the variants of coronaviruses circulating in the communities. Wastew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Although the PCR-based methods can provide timely and cost-effective estimation of disease prevalence, it is incapable of targeting emerging variants and providing genetic information to track virus evolution. 12,15,[34][35][36] In contrast, the ATOPlex sequencing method not only enables accurate quantification of the RNA concentration in wastewater but is also capable of identifying the co-occurrence of different VOCs, thus demonstrating wastewater as a valuable tool to monitor disease trends and variant dynamics in the community. This study found a stronger Pearson's correlation between ATOPlex sequencing and number of daily new cases compared to the PCR-based method, particularly in the LG region (The correlation coefficients (|r|) for ATOPlex, N1, and N2 in relation to the daily new cases were found to be 0.66, 0.38, and 0.23, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although the PCR-based methods can provide timely and cost-effective estimation of disease prevalence, it is incapable of targeting emerging variants and providing genetic information to track virus evolution. 12,15,[34][35][36] In contrast, the ATOPlex sequencing method not only enables accurate quantification of the RNA concentration in wastewater but is also capable of identifying the co-occurrence of different VOCs, thus demonstrating wastewater as a valuable tool to monitor disease trends and variant dynamics in the community. This study found a stronger Pearson's correlation between ATOPlex sequencing and number of daily new cases compared to the PCR-based method, particularly in the LG region (The correlation coefficients (|r|) for ATOPlex, N1, and N2 in relation to the daily new cases were found to be 0.66, 0.38, and 0.23, respectively.…”
Section: Discussionmentioning
confidence: 99%